PENGEMBANGAN BAHAN AJAR MATERI CERPEN BERBASIS FLIPBOOK DIGITAL UNTUK SISWA KELAS V SD PADMAJAYA PALEMBANG - Damayanti, Adilla Fitri; Murniviyanti, Liza; Pratama, Aldora (Faculty of Teacher Training and Education, 2024)
This research aims to produce a digital flipbook-based short story teaching material product for fifth grade elementary school students that is valid, practical and effective. This research uses research and development methods with the ADDIE development model which consists of five stages, namely the analysis stage, planning stage, development stage, implementation stage and evaluation stage. The subjects in this research were fifth grade students at Padmajaya Elementary School, Palembang. Data collection for this research was obtained from validation questionnaires, student response questionnaires and tests. The results of data analysis based on validation of digital flipbook-based short story teaching materials carried out by experts consisting of media experts, material experts and language experts obtained an average validation score with a percentage of 81,8% with the category very valid and suitable for use at this stage. trials. Based on the results of the One to One questionnaire, the percentage score was 93,3% in the very practical category and the Small Group results obtained a percentage score of 94,5% in the very practical category. Then the test results of students using digital flipbook-based short story teaching materials obtained a percentage score of 0,908% in the very effective category. Based on the results developed by the researchers, it was concluded that the development of digital flipbook-based short story teaching materials for fifth grade students at Padmajaya Elementary School, Palembang, met the criteria of being valid, practical, effective and suitable for use in the process of learning Indonesian short story material.